Readjustment of abdominal computed tomography protocols in a university hospital: impact on radiation dose - Romano,Ricardo Francisco Tavares (2015)
AbstractObjective:To assess the reduction of estimated radiation dose in abdominal computed tomography following the implementation of new scan protocols on the basis of clinical suspicion and of adjusted images acquisition parameters.Materials and Methods:Retrospective and prospective review of reports on radiation dose from abdominal CT scans performed three months before (group A – 551 studies) and three months after (group B – 788 studies) implementation of new scan protocols proposed as a function of clinical indications. Also, the images acquisition parameters were adjusted to reduce the radiation dose at each scan phase. The groups were compared for mean number of acquisition phases, mean CTDIvol per phase, mean DLP per phase, and mean DLP per scan.Results:A significant reduction was observed for group B as regards all the analyzed aspects, as follows: 33.9%, 25.0%, 27.0% and 52.5%, respectively for number of acquisition phases, CTDIvol per phase, DLP per phase and DLP per scan (p < 0.001).Conclusion:The rational use of abdominal computed tomography scan phases based on the clinical suspicion in conjunction with the adjusted images acquisition parameters allows for a 50% reduction in the radiation dose from abdominal computed tomography scans.